2021
DOI: 10.1371/journal.pone.0257510
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA gives comparable results to morphology-based indices of macroinvertebrates in a large-scale ecological assessment

Abstract: Anthropogenic activities are changing the state of ecosystems worldwide, affecting community composition and often resulting in loss of biodiversity. Rivers are among the most impacted ecosystems. Recording their current state with regular biomonitoring is important to assess the future trajectory of biodiversity. Traditional monitoring methods for ecological assessments are costly and time-intensive. Here, we compared monitoring of macroinvertebrates based on environmental DNA (eDNA) sampling with monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…For example, we identified that the relative abundance of 81 OTU-based indicators was strongly associated with different human disturbance groups (range from 1 to 100 times), although only 37 of them have clear classification at the genus or species level. This result indicates that OTU-based indicators can make up for the deficiency of the traditional species annotation strategy to a great extent because the traditional strategy is limited to the part of biodiversity with obvious morphological characteristics, which often has high coverage of public reference sequences, such as fish and birds. , Recent studies have indeed found that for well-studied groups, eDNA-based assessments give comparable results with respect to ecological indices. , Although eDNA metabarcoding may reduce cost and is a less invasive sampling process, ,, the deficiency of reference databases and the deviation of OTU species annotation are still one of the biggest shortcomings of this method. An OTU-based indicator strategy obviously reduces or bypasses the dependence of species annotation on reference databases .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, we identified that the relative abundance of 81 OTU-based indicators was strongly associated with different human disturbance groups (range from 1 to 100 times), although only 37 of them have clear classification at the genus or species level. This result indicates that OTU-based indicators can make up for the deficiency of the traditional species annotation strategy to a great extent because the traditional strategy is limited to the part of biodiversity with obvious morphological characteristics, which often has high coverage of public reference sequences, such as fish and birds. , Recent studies have indeed found that for well-studied groups, eDNA-based assessments give comparable results with respect to ecological indices. , Although eDNA metabarcoding may reduce cost and is a less invasive sampling process, ,, the deficiency of reference databases and the deviation of OTU species annotation are still one of the biggest shortcomings of this method. An OTU-based indicator strategy obviously reduces or bypasses the dependence of species annotation on reference databases .…”
Section: Discussionmentioning
confidence: 95%
“…58,59 Recent studies have indeed found that for well-studied groups, eDNA-based assessments give comparable results with respect to ecological indices. 60,61 Although eDNA metabarcoding may reduce cost and is a less invasive sampling process, 23,62,63 the deficiency of reference databases and the deviation of OTU species annotation are still one of the biggest shortcomings of this method. An OTU-based indicator strategy obviously reduces or bypasses the dependence of species annotation on reference databases.…”
Section: Discussionmentioning
confidence: 99%
“…Successful detection using an eDNA metabarcoding approach is underpinned by the primers used to amplify target species. However, due to the traditional methods, which previously established the ‘freshwater macroinvertebrate’ group, this refers to detecting a polyphyletic group (Brantschen et al, 2021; Carew, Miller, & Hoffmann, 2011; Leese et al, 2021), which makes finding a conserved primer region for multiple groups difficult. Here, we used one general metazoan primer pair for the CO1 marker (Leray et al, 2013; Geller et al, 2013), which may not be ideal for the successful detection of some of the target IAS.…”
Section: Discussionmentioning
confidence: 99%
“…After bioinformatic quality assurance, each dataset was subject to further quality assurance steps for tag‐jumping or minor contamination in library preparation. For the national samples, only ZOTUs, which appeared in at least two out of the four replicates, were kept (See Brantschen, Blackman, Walser, & Altermatt, 2021 for full details). For the catchment sampling campaign, 0.1% of reads in each sample were removed from each taxon found in that sample, in line with other studies (Hänfling et al, 2016, see Blackman et al, 2021 for full details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation